Gestão estratégica de indicadores aplicada a uma instituição de ensino superior confessional - Meinertz, Carmo André (Universidade do Vale do Rio dos Sinos, 2019)
The objective of this work is to propose a scorecard to measure key performance indicators and assist the management of a higher education institution (HEI) to successfully implement its mission. It applies concepts of strategic management, adopting the balanced scorecard as a driver for the development of a strategic indicators from the HEI through KPM (Key Performance Management) modeling, with a set of key indicators that express the main results to be followed by the institution. The studied institution is a non-profit, philanthropic, catholic confessional, higher education institution, localized in Caxias do Sul. The research is of exploratory nature, with qualitative approach, using the case study method. Documentary survey was one of the data collection approach, besides a file survey and semi-structured interviews with the HEI managers. We analyzed files that could indicate the adequate indicators to monitor the strategic management of the organization and interviewed the managers to identify their specific-indicators necessity, and their expertise in relation to this theme. After this, summarization and literature revision were performed, with the aim of developing a set of indicators to monitor the HEI strategy and fulfill its mission. The set of indicators was proposed based on the BSC methodology, segmented on the following perspectives: Financial; Clients; Processes; Learning and Developing, but, considering the institution’s peculiarity, Social Responsibility and Higher Education was also included. These perspectives are constituted by 22 indicators, disposed in a way to monitor the organization’s performance, as a way to fulfill and achieve its Strategic Planning.
Keywords: Indicadores de Gestão; Estratégia; Ensino Superior; Instituição Educacional Confessional; Performance Indicators; Strategy; Higher Education; Confessional Educational Institution; ACCNPQ::Ciências Humanas::Educação